2018
DOI: 10.9734/jamcs/2018/44336
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamics of Banana Xanthomonas Wilt Transmission Incorporating Infectious Force in both Asymptomatic and Symptomatic Stages

Abstract: Despite massive efforts by regional governments and partners in the East and Central African region towards fighting Xanthomonas Wilt of banana, the disease is reported to continue to spread to new areas and resurge in others it had been contained. The use of asymptomatic but infectious plants is hypothesized to play a leading role in the persistence of the disease and it's introduction to new areas. A model for the transmission of BXW by symptomless plants is proposed and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Nakakawa et al [12] considered the vertical and vector mode transmissions in the BXW dynamical model. Kweyunga et al [13] developed a model of BXW considering both horizontal and vertical modes of transmission. In [14], the authors derived a non-linear model to analyze the role of neglected control measures in the BXW transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakakawa et al [12] considered the vertical and vector mode transmissions in the BXW dynamical model. Kweyunga et al [13] developed a model of BXW considering both horizontal and vertical modes of transmission. In [14], the authors derived a non-linear model to analyze the role of neglected control measures in the BXW transmission.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the aforementioned studies of mathematical modeling of the BXW disease [9][10][11][12][13][14] have yet to be analyzed using fractional derivatives. In this paper, we generalize the non-linear control-based model of BXW [14] by using Caputo fractional derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that there of no tool based transmission, the study further indicated that controlling inflorescence infection and roguing regularly eliminate the BXW disease on the farm. Furthermore, Kweyunga et al [27] developed a mathematical model to study the transmission dynamics of BXW disease. The study considered both horizontal and vertical modes of transmission and included forces of infection from both asymptomatic and symptomatic infected banana plants.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that parameters from asymptomatic infected banana plants are more sensitive to the basic reproduction number. Moreover, Mapinda et al [28] modified the model by Kweyunga et al [27] to include contaminated soil. The results showed that soil inoculum plays an important role in the persistence of the disease in the farm setting.…”
Section: Introductionmentioning
confidence: 99%